Comparative transcriptome profiles of large and small bodied large-scale loaches cultivated in paddy fields - Liulan Zhao (Nature Portfolio, 2021)
Abstract Fish culture in paddy fields is a traditional aquaculture mode, which has a long history in East Asia. Large-scale loach (Paramisgurnus dabryanus) fast growth is suitable for paddy fields aquaculture in China. The objective of this study was to identify differential expression genes (DEGs) in the brain, liver and muscle tissues between large (LG, top 5% of maximum total length) and small (SG, top 5% of minimum total length) groups using RNA-seq. In total, 150 fish were collected each week and 450 fish were collected at twelfth week from three paddy fields for all the experimental. Histological observation found that the muscle fibre diameter of LG loaches was greater than that of SG loaches. Transcriptome results revealed that the high expression genes (HEGs) in LG loaches (fold change ≥ 2, p < 0.05) were mainly concentrated in metabolic pathways, such as “Thyroid hormone signalling pathway”, “Citrate cycle (TCA cycle)”, “Carbon metabolism”, “Fatty acid metabolism”, and “Cholesterol metabolism”, and the HEGs in SG loaches were enriched in the pathways related to environmental information processing such as “Cell adhesion molecules (CAMs)”, “ECM− receptor interaction” and “Rap1 signalling pathway”; cellular processes such as “Tight junction”, “Focal adhesion”, “Phagosome” and “Adherens junction”. Furthermore, IGFs gene family may play an important role in loach growth for their different expression pattern between the two groups. These findings can enhance our understanding about the molecular mechanism of different growth and development levels of loaches in paddy fields.